2007
DOI: 10.4049/jimmunol.179.6.3680
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Dioxide Promotes Allergic Sensitization to Inhaled Antigen

Abstract: Allergen sensitization and allergic airway disease are likely to come about through the inhalation of Ag with immunostimulatory molecules. However, environmental pollutants, including nitrogen dioxide (NO2), may promote adaptive immune responses to innocuous Ags that are not by themselves immunostimulatory. We tested in C57BL/6 mice whether exposure to NO2, followed by inhalation of the innocuous protein Ag, OVA, would result in allergen sensitization and the subsequent development of allergic airway disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 56 publications
7
81
1
2
Order By: Relevance
“…Alberg et al (2011) were not able to detect an impact of NO 2 on allergy induced by ovalbumin, whereas diesel exhaust particles were shown to be a potent adjuvant. In contrast, Bevelander et al (2007) and Hodgkins et al (2010) did find a potentiating effect of NO 2 within the concentration range used by Alberg et al (2011) (5-25 ppm) when NO 2 exposure occurred immediately beforehand and ovalbumin exposure was by inhalation. Recent in vitro findings suggested that levels of SO 2 and NO 2 below current EU health based exposure standards can exacerbate pollen allergy on susceptible subjects (Sousa et al, 2012).…”
Section: Pmmentioning
confidence: 44%
“…Alberg et al (2011) were not able to detect an impact of NO 2 on allergy induced by ovalbumin, whereas diesel exhaust particles were shown to be a potent adjuvant. In contrast, Bevelander et al (2007) and Hodgkins et al (2010) did find a potentiating effect of NO 2 within the concentration range used by Alberg et al (2011) (5-25 ppm) when NO 2 exposure occurred immediately beforehand and ovalbumin exposure was by inhalation. Recent in vitro findings suggested that levels of SO 2 and NO 2 below current EU health based exposure standards can exacerbate pollen allergy on susceptible subjects (Sousa et al, 2012).…”
Section: Pmmentioning
confidence: 44%
“…Overweight and obese children are more susceptible to indoor air pollutants, especially particulate matter and nitrogen dioxide, than are lean children (63). We have reported that in nonobese mouse models, nitrogen dioxide inhalation causes allergic asthma-like disease through NLRP3 and IL-1 signaling (64) and inherent asthma-like disease through activation of the transcription factor nuclear factor-kB (NF-kB) in the airway epithelium (65). Airway epithelial NF-kB activation increases methacholine responsiveness (in the absence of allergen exposure) by increasing the abundance of airway smooth muscle (66), increases lung type 2 innate lymphoid cells, and facilitates allergic antigen sensitization (67,68).…”
Section: Irritant-and Pollutioninduced Asthma In Obesitymentioning
confidence: 99%
“…Exposure to NO 2 positively correlates with asthma severity, the risk of hospitalization, disease exacerbation, the risk of death, and the development of asthma in previously healthy children (8)(9)(10). We have reported that NO 2 exposure allergically sensitizes mice to ovalbumin (OVA; we define sensitization as the act or process of inducing an acquired allergy), inducing methacholine airway hyperresponsiveness (AHR), antigen-specific IgG1 and IgE, inflammatory leukocyte recruitment to the airway, and the production of Th2 cytokines and IL-17 during in vitro restimulation of CD4 1 T cells (11,12). Th17 cells comprise a distinct subset of T cell receptor (TCR)ab 1 CD4 1 T cells that are characterized by the production of IL-17A, IL-17F, and IL-22 and the transcription factor retinoic acid receptor-related orphan receptor (ROR)gt.…”
Section: T Cell Receptor (Tcr)bmentioning
confidence: 99%
“…NO 2 exposure rapidly leads to NF-kB activation in airway epithelia, and later, the up-regulation of Saa3 and the production of SAA3 from airway epithelia (6,11,28). SAA is a candidate downstream mediator of NO 2 -promoted allergic sensitization (6,28,49).…”
mentioning
confidence: 99%